KONSEP PERANCANGAN DAN PENGEMBANGAN SARANA DAN MEDIA PEMBELAJARAN DI KABUPATEN SIDOARJO - Mohamad Febry Ardiansyah; Failasuf Herman Hendra; Siti Azizah (Institut Teknologi Adhi Tama Surabaya, 2022)
Sidoarjo Regency as one of the buffers for the capital city of East Java Province is an area that is experiencing rapid development in the education sector. Tutoring program to develop study habits that develop in the era of globalization where the challenges and competition to obtain the best formal education is getting tougher and competitive. Facilities in the form of learning facilities and media are needed to improve the quality of education in Sidoarjo Regency.The design and development of learning facilities and media carries the theme of Green Architecture which is then revealed to the macro concept of